Asian art therapists : navigating art, diversity and culture - Kitazawa, Megu (New York, NY : Routledge, 2021)
"This book explores Asian art therapist experiences in a predominantly white professional field, challenging readers with visceral, racial, and personalized stories that may push them far beyond their comfort zone. Drawing from the expertise and practices of Asian art therapists from around the world, this unique text navigates how minority status can affect training and clinical practice in relation to clients, co-workers, and peers. It describes how Asian pioneers have broken therapeutic and racial rules to accommodate patient needs and improve clinical skills and illustrates how the reader can examine and disseminate their own biases. Authors share how they make their own path - by becoming aware of the connection between their lives and circumstances - and how they liberate themselves and those who seek their services. This informative resource for art therapy students and professionals offers non-Asian readers a glimpse at personal and clinical experiences in the White-dominant profession while detailing how Asian art therapists can lead race-based discussions with empathy to become more competent therapists and educators in an increasingly diversifying world"--
OCLC-licensed vendor bibliographic record.
Keywords: Art therapy -- Cross-cultural studies; Arts -- Therapeutic use -- Cross-cultural studies; Psychotherapists -- Attitudes; Asian Americans -- Psychology; PSYCHOLOGY / Psychotherapy / Counseling; ART / Asian